EFEKTIVITAS TEKNIK Discrete Trial Training (DTT) UNTUK MENINGKATKAN KEMAMPUAN MENGENAL WARNA PRIMER BAGI ANAK AUTIS X DI SLB AUTISMA MUTIARA BANGSA PADANG - Gusnanda Amalia (Universitas Negeri Padang, 2015)
This research is motivated by the discovery of an autistic child in SLB Autisma Mutiara Bangsa Padang that has not been able to recognize primary colors. While school teacher has been giving lessons on letters and numbers, whereas in the curriculum the child should already know basic colors in the development phase before the commencing of cognitive learning. Teachers also less consistent with the techniques used or the stages of the curriculum in delivering learning. Based on such facts, the researchers aim to prove whether the Discrete Trial Training (DTT) technique is effective to improve the ability of the child to know the primary colors. This type of research is the single subject research (SSR), with A-B-A design and research data analysis using visual analysis chart.Data analysis showed the baseline (A1) is performed as much as 7 times with mean level of 0%, the stability percentage of 100%, tendency towards stable (=). Continued intervention (B) for 16 times with mean level of 59.37%, 18.75% stability percentage, tendency toward increased (+). Further baseline condition (A2) is performed as much as 7 times with mean level of 90.47%, 28.57% stability percentage, tendency towards increased (+). Inter-state analysis of the data obtained changes in condition B/A1 is +0, and A2/B is +100. Overlap on data analysis B/A1 and B/A2 is 12.5% and 12.5%, respectively. Thus the research hypothesis is accepted, which Discrete Trial Training (DTT) technique is effective in improving the ability of autistic children recognize primary colors in SLB Autisma Mutiara Bangsa Padang. Key Word: primary colors; discrete trial training; autistic; autism